2012
DOI: 10.4161/onci.21990
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells expand during breast cancer progression and promote tumor-induced bone destruction

Abstract: Myeloid-derived suppressor cells (MDSCs), identified as Gr1+CD11b+ cells in mice, expand during cancer and promote tumor growth, recurrence and burden. However, little is known about their role in bone metastases. We hypothesized that MDSCs may contribute to tumor-induced bone disease, and inoculated breast cancer cells into the left cardiac ventricle of nude mice. Disease progression was monitored weekly by X-ray and fluorescence imaging and MDSCs expansion by fluorescence-activated cell sorting. To explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 32 publications
7
96
1
Order By: Relevance
“…It has been previously shown that MDSC populations expand in athymic mice bearing TNBC xenografts, specifically MDA-MB-231, during tumor development (26). The chemotactic role of IL-8 toward immune cell populations includes the ability of this chemokine to recruit MDSCs to the tumor microenvironment (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that MDSC populations expand in athymic mice bearing TNBC xenografts, specifically MDA-MB-231, during tumor development (26). The chemotactic role of IL-8 toward immune cell populations includes the ability of this chemokine to recruit MDSCs to the tumor microenvironment (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, different mechanisms appear to be used by the two subgroups of MDSCs, with M-MDSCs mediating immune suppression via expression of high levels of ARG-1 and iNOS and PMN-MDSCs mainly producing high levels of ROS (60). While initially characterized in mouse cancer models (61), expansion of MDSCs is known to take place in many solid tumor types, including breast cancer (26), and high numbers of MDSCs are detected in the peripheral blood of cancer patients, particularly in advanced stages of disease, compared with blood of healthy donors (62). The study of the mechanisms involved in the tumor recruitment of MDSCs has led to the understanding that homing of M-MDSCs is mainly dependent upon the activation of the CCL2/CCR2 axis, while attraction of PMN-MDSCs has been mostly associated with signaling via the CXCR2 receptor, which is in agreement with the predominant expression of CXCR1 and CXCR2 in PMN-MDSCs, as compared with the prevalence of CCR2 expression in M-MDSC populations (63).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MDSC were present at a higher frequency in IRF-8 KO tumorbearing mice. These cells have been identified as important indicators of conditions that favor tumor growth (Danilin et al, 2012;Gabrilovich et al, 2012). Interestingly, IRF-8 was recently shown to be directly involved in MDSC development (Waight et al, 2013); these findings are of extreme relevance, as they provide support for a possibility that IRF-8 might orchestrate chemokine-chemokine receptor patterns in the tumor microenvironment and so modulate immune cell infiltration.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Mouse MDSC consist of a heterogeneous population distinct from immature myeloid cells present in tumor-free mice. Two main MDSC subsets have been described: the monocytic subset (mMDSC, CD11b…”
Section: Gr1mentioning
confidence: 99%